ASSESSMENT OF WATER COLLECTED FROM BOREHOLES WITHIN UNSANITARY LANDFILL IN ANAMBRA STATE - Aralu, CHIEDOZIE; Okoye, Patrich-Anthony; Ezugwu, John; Eboagu, Nkiruka (European Journal of Applied Sciences, 2021)
Leachate infiltration from indiscriminate dumping of refuse has been a course of concern to the public. These leachates are a source of organic or inorganic pollutants to the underground water which poses health-associated risks to the public. The present study aims to determine the physicochemical properties and quality levels of boreholes located within the unlined dumpsite environment. Thirty-two borehole samples (sixteen upstream and sixteen downstream samples) were collected within the dumpsite environment. The upstream samples are closer to the dumpsite, while the downstream(control) is far away from the dumpsite. The physicochemical parameters were assessed using American Public Health Association standard methods. The quality of the boreholes was compared using the WHO allowable threshold. The result revealed that nitrites, chemical oxygen demand, and biochemical oxygen demand values exceeded the WHO drinking water limits for both locations which can constitute environmental and public health problems. The upstream sample’s physicochemical characteristics values were greater than the downstream samples based on its closeness to the landfill. The seasonal variation revealed that the wet season values were significantly greater than the dry season values due to the percolation of leachates from the dumpsite during the rainy season. It is concluded that indiscriminate dumping of refuse using unlined dumpsite practices within the residential neighbourhood can damage the environment and induce public health risks of the residents.